2018
DOI: 10.1002/ese3.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the liquid vapor oxygen transfer coefficient (kLα) on ethanol production from cassava residue and analysis of the fermentation kinetics

Abstract: Cassava residue is the solid waste generated from the production of tapioca starch and has considerable reuse value. In this study, cassava residue was examined as a hydrolysate for ethanol production, and the effects of different liquid phase oxygen transfer coefficients (k L α) on the production of ethanol from cassava residue hydrolysates were studied. Based on analyses of dissolved oxygen and a set of optimal experimental schemes, dynamic models of cell growth and product synthesis were optimized, using MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The total acid was titrated using an acid-base method. The ethanol content was determined using a 7890A gas chromatography (GC) detection system (Agilent, State of California, USA) equipped with an Aminex DB-624 25 m × 0.200 mm column (Agilent, USA), in accordance with previous methods (Li et al, 2018). The reducing sugar content was measured using a DNS kit (Solarbio, Beijing, China).…”
Section: Determination Of Total Acid Ethanol Reducing Sugar and Free ...mentioning
confidence: 99%
“…The total acid was titrated using an acid-base method. The ethanol content was determined using a 7890A gas chromatography (GC) detection system (Agilent, State of California, USA) equipped with an Aminex DB-624 25 m × 0.200 mm column (Agilent, USA), in accordance with previous methods (Li et al, 2018). The reducing sugar content was measured using a DNS kit (Solarbio, Beijing, China).…”
Section: Determination Of Total Acid Ethanol Reducing Sugar and Free ...mentioning
confidence: 99%
“…22,23 OTR (K L α), an important index for simulating aerobic cell reaction process and reactor design and amplification. 24,25 Therefore, optimizing the two factors, C* À C L and K L α, could be the main strategy to improve OTR. On the other hand, to improve the driving force of mass transfer C* parameter should be increased, mainly by reducing biocatalysis temperature, changing broth solute, and increasing oxygen partial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…K L represents the oxygen mass transfer coefficient driven by concentration difference (m/h); α represents the specific surface area (m 2 /m 3 ); C * represents the saturated DO concentration (mmol/L); C L represents the DO concentration in the broth (mmol/L); C * − C L means the difference of oxygen concentration, which is the driving force affecting the transfer rate. Moreover, in industry, K L and α are combined into one parameter, designed as volume transfer coefficient ( K L α ), an important index for simulating aerobic cell reaction process and reactor design and amplification 24,25 . Therefore, optimizing the two factors, C * − C L and K L α , could be the main strategy to improve OTR.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have usually focused on the laminar flow mode system, and the bubble behaviors were not be considered. [10][11][12][13][14][15] Hu et al 16 found that threshold values for mammalian cells growing in suspension cover a wide range of from 8 to 450 Pa and cannot obtain a precise value. Nienow et al 17 indicted that if hydrodynamic stress is lower than critical value, it makes no effect on cell growth; however, the negative response will result in the slower growth, change of metabolism, etc, when it exceeds over threshold value.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Hu et al 16 found that threshold values for mammalian cells growing in suspension cover a wide range of from 8 to 450 Pa and cannot obtain a precise value. [10][11][12][13][14][15] Hu et al 16 found that threshold values for mammalian cells growing in suspension cover a wide range of from 8 to 450 Pa and cannot obtain a precise value.…”
mentioning
confidence: 99%